The Time Consistency of Optimal Monetary and Fiscal Policies - Alvarez, Fernando; Kehoe, Patrick J.; Neumeyer, Pablo Andres (Econometrica, 2004)
We show that optimal monetary and fiscal policies are time consistent for a class of economies often used in applied work, economies appealing because they are consistent with the growth facts. We establish our results in two steps. We first show that for this class of economies, the Friedman rule of setting nominal interest rates to zero is optimal under commitment. We then show that optimal policies are time consistent if the Friedman rule is optimal. For our benchmark economy in which the time consistency problem is most severe, the converse also holds: if optimal policies are time consistent, then the Friedman rule is optimal.